Agronomical evaluation of the Spanish Barley core collection - Yahiaoui S.; Gracia M.P.; Igartua E.; Medina B.; Ciudad F.J.; Codesal P.; Molina-Cano J.L.; Lasa J.L. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
Spanish barleys constitute an underused resource which shows distinct genetic, morphologic, and agronomic traits. The Spanish Barley Core Collection (SBCC) was assembled as a manageable tool to study this genetic diversity. It is constituted by 159 landrace-derived inbred lines (148 six-row and 11 two-row), plus 16 old varieties (8 two-row, 8 six-row) extensively grown in Spain in the 20th century. An extensive evaluation of the SBCC was carried out throughout the country across a range of environments (10 trials, from 5 locations across Aragón, Castilla y León, and Cataluña, over 3 years). A set of 10 modern cultivars was included in the trials as checks. A range of agronomic (yield, heading date, plant height, lodging, thousand kernel weight, test weight, spikes m-2, kernels m-2, kernels spike-1), disease resistance (net blotch, leaf rust, powdery mildew), and malting quality traits (kernel plumpness, screening, malt extract and protein content) were evaluated. Not all traits were evaluated at all trials. Climatic data available from meteorological stations close to each trial were collected and used to interpret genotype by environment interaction by factorial regression.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)